Choice of law and validity of arbitration agreements: a comparative analysis - Potrubach, Natalia (Riga Graduate School of Law, 2024)
This bachelor thesis explores the interplay between the validity of arbitration agreements and the choice of law issues. The aim of the present thesis is to analyse and compare the legal frameworks governing these two crucial aspects of international commercial arbitration, considering the perspectives of different jurisdictions and international conventions. The study objectives contain the following: First, to analyse the normative documents approving the validity of international arbitration agreements and the procedure for selecting the law applicable to such agreements. Second, to examine these issues through the prism of the national legislations of England and France. Third, to find out to what extent and when these areas (law applicable and validity of the agreement with further enforceability) can be and are interrelated. And, fourth, to find out what influence the law applicable to the agreement has on its validity. The main results of the thesis include the following: The law applicable to the arbitration agreement indeed can have a great influence on the validity of the agreements. However, it is worth noting that national law in turn determines part of crucial issues, such as the issues of legal capacity affecting validity. At the same time, this thesis does not explore investment arbitration and the peculiarities of Eastern legal systems, which may serve as a basis for further research.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Arbitration; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; International commercial arbitration; choice of law; UNICITRAL Model law; New York Convention